2019
DOI: 10.1021/acs.est.9b05669
|View full text |Cite
|
Sign up to set email alerts
|

Triphenyl Phosphate at Environmental Levels Retarded Ovary Development and Reduced Egg Production in Japanese Medaka (Oryzias latipes)

Abstract: Since triphenyl phosphate (TPhP) elicits both antiestrogenic activities via blocking the estrogen receptor (ER) and estrogenic activity by elevating 17β-estradiol (17β-E2) synthesis, its adverse effect on female reproduction is uncertain. In this study, we exposed Japanese medaka to TPhP at 131, 363, and 1773 ng/L for 100 days following hatching. TPhP significantly induced ovary retardation in all exposure groups (incidence: from 11.9 to 37.8%) and reduced egg production by 38.9 and 50.9% in the 363 and 1773 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…The time-point-sampled embryos collected in seven days were pooled to obtain sufficient embryos to determine the embryonic concentrations of EHDPP and its metabolite. After 35 days of exposure, the females were sacrificed, and the brain, liver, muscles, and ovary were sampled as described in our previous study 33 to determine EHDPP concentrations for better understanding the maternal transfer of EHDPP and whether the exposure level used in this study is comparable with those reported in wild fish. The detailed experimental design can be found in Figure S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The time-point-sampled embryos collected in seven days were pooled to obtain sufficient embryos to determine the embryonic concentrations of EHDPP and its metabolite. After 35 days of exposure, the females were sacrificed, and the brain, liver, muscles, and ovary were sampled as described in our previous study 33 to determine EHDPP concentrations for better understanding the maternal transfer of EHDPP and whether the exposure level used in this study is comparable with those reported in wild fish. The detailed experimental design can be found in Figure S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As we all know, reproductive ability is essential for the continuation of a population, and the number of a population is also of great signi cance to the stability of the ecosystem (Arcand-Hoy and Benson, 1998; Nassar and Fahmy, 2016). However, environmental pollutants often induced reproductive toxicity by interfering with gamete formation, such as bisphenol compounds (Ji et (Li et al, 2019b). In vertebrates, sexual behavior coordinates the release of gametes to determine fertility (Mitchell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2018 ; Meeker and Stapleton 2010 ; Meeker et al. 2013 ), water ( Li et al. 2019a ), or air ( Wei et al.…”
Section: Introductionmentioning
confidence: 99%